61‐2: Color Gamut of Multi‐Chromatic Displays. Issue 1 (29th May 2019) - Masaoka, Kenichiro; Jiang, Fu; Fairchild, Mark D.; Heckaman, Rodney L.
Abstract : It is said that multi‐chromatic displays can achieve wider color gamut by using saturated color channels, while there are also claims that these displays lose brightness and/or color saturation for higher luminance colorful images. This topic has created some controversy in the display industry and at standards‐setting organizations. This research examines color gamut volumes for a variety of simulated "multi‐chromatic" or "multi‐primary" (incorrect term) displays with combinations of cyan, magenta, and yellow color channels and/or white color channels. A two‐dimensional representation of color gamuts (i.e., gamut rings) illustrates that adding non‐primary color channels to a tri‐chromatic (red, green, and blue color channel) display reduces the overall chroma of color images at brighter levels.